1989
DOI: 10.1111/j.1365-2915.1989.tb00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and cross‐resistance in guinea‐pigs and rabbits to immature stages of ixodid ticks

Abstract: Infestation of guinea-pigs and rabbits with larvae of any one of five species of ticks, Rhipicephalus appendiculatus Neumann, Rhipicephalus evertsi evertsi Neumann, Amblyomma hebrauem Koch, Amblyomma variegatum Fabricius and Ixodes ricinus L., conferred resistance in the animals when exposed to subsequent infestations with the same tick species. Resistance to infestations by other tick species was not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…However, some studies did not find cross-immunity against different parasite species (e.g. Rechav et al, 1989). Apparently, the occurrence of cross-I.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, some studies did not find cross-immunity against different parasite species (e.g. Rechav et al, 1989). Apparently, the occurrence of cross-I.…”
Section: Discussionmentioning
confidence: 98%
“…S. Khokhlova and others McTier et al (1981) showed that in guinea pigs, cross-immunity occurred between two ticks of Dermacentor genus but not between ticks belonging to Dermacentor and Amblyomma genera. Rabbits demonstrated cross-resistance between two ticks of Hyalomma genus (Kumar and Kumar, 1996), but not between Rhipicephalus and Ixodes genera (Rechav et al, 1989). Furthermore, cross-immunity between two Rhipicephalus species was reported for rabbits (Njau and Nyindo, 1987), whereas no cross-immunity between these two ticks was found in guinea pigs (Rechav et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although acquired resistance to tick feeding is species specific, examples of cross-resistance to infestations with different tick species are well-known [30][31][32][33][34][35]. Cross-resistance appeared between Metastriata species, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…During repeated infestation with other tick species, lowered efficiency of some physiological processes, first of all of feeding, maturation and oviposition processes [34,[37][38][39][40][41], embryonic development, as well as larval hatching and molting of the subsequent developmental stages [42][43][44] were observed. Moreover, lethality of the active tick stages was increased (unpublished data).…”
Section: Discussionmentioning
confidence: 99%